Historias ilustradas para dar visibilidad a la ansiedad - Riaño Roa, Angie Mariana (Universidad Antonio Nariño, 2025)
This project presents a physical book that brings together five personal stories of young people aged 18 to 25 from the Antonio Nariño University diagnosed with anxiety, who constitute the target audience. The average age of the study population is 20 years old, and 58% have been diagnosed with anxiety.